Biodiversity Governance Outside Protected Areas in the Context of Other Effective Area-Based Conservation Measures (OECMs): A Systematic Review - Sigdel, Ekraj; Joshi, Khagendra Prasad; Regmi, Aayoush Raj; Jnawali, Shant Raj; Baral, Sony; Khanal Chhetri, Bir Bahadur (Banko Janakari, 2025)
The Other Effective Area-Based Conservation Measures (OECMs) have recently been recognized as a viable tool for conserving biodiversity beyond protected areas. As a new concept, it is essential to evaluate the current knowledge on OECMs and their prospects for conserving biodiversity resources outside protected areas. We conducted a systematic review of the literature on key concepts, including OECMs, governance, and biodiversity, using the Publish or Perish Software Program in Google Scholar. Out of the total 200 articles identified through the keywords, 54 were shortlisted for a comprehensive full-text review. Based on the closeness of the study objectives to our research questions, 27 articles were selected for detailed analysis. As no journal articles related to the OECM in Nepal were found within the set time frame, contemporary policies and legal documents of Nepal were also reviewed. Additionally, to account for the lengthy publication process, a few more recent journal articles were also reviewed. The review revealed that nearly half of the studies (13) focused on global and regional scales, while eight studies were conducted in eight different countries, and two studies in each of three additional countries. Recent studies on the integration of OECM principles in Nepal’s forestry sector policies and practices were also reviewed. Community-led conservation, supported by coordination and collaboration among multilevel governance systems - including both state and non-state actors-has been found effective in conserving biodiversity resources outside protected areas. However, further studies on natural resources governance beyond protected areas are needed to ensure long-term in-situ conservation of biodiversity through the OECM model.